Iron, vitamin B12 and folate. (April 2017) - Moll, Rachel; Davis, Bernard
Abstract: Iron, vitamin B12 and folate are required for essential metabolic functions. Deficiency states of these nutrients, either singly or in combination, are common clinical conditions. Clinically, they present with not only disordered haematopoiesis, but also widespread effects in other organs that can precede the appearance of haematological abnormalities. Investigation of suspected iron, vitamin B12 or folate deficiency should first be directed at establishing that the deficiency state exists, but this can be challenging because of the limitations of available biomarkers for evaluating tissue status. A careful assessment of clinical symptoms and signs is indispensable to guide appropriate requesting and interpretation of relevant laboratory tests. Every effort should be made to determine the cause of the nutritional deficiency and to treat it where possible. Correcting the deficiency with supplements is usually straightforward, provided adherence to treatment is ensured. Blood transfusion should be avoided unless symptoms dictate otherwise.